2008
DOI: 10.1007/s10531-008-9539-5
|View full text |Cite
|
Sign up to set email alerts
|

Species richness, abundance, rarity and environmental gradients in coastal barren vegetation

Abstract: Coastal barrens in Nova Scotia are heathlands characterised by short, predominantly ericaceous vegetation, sparse tree cover, exposed bedrock, pockets of Sphagnum bog, and stressful climatic conditions. Although coastal barrens are prominent in the physical and cultural landscape, they are largely unprotected. We selected six barrens along the Atlantic coast, and surveyed 20 1-m 2 plots at each barren for vascular plants, macrolichens, mosses and environmental factors. We recorded 173 species (105 vascular, 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 82 publications
0
42
1
Order By: Relevance
“…Heathland is a traditional habitat in Western Europe (De Smidt 1979;Webb 1998) and parts of Northern America (Oberndorfer and Lundholm 2009) with very characteristic plants and animals (Delettre et al 2008;Lin et al 2007;Maes et al 2003;Telfer and Eversham 1996). In most countries, the present area covered with this vegetation type is only a fraction of the area covered around 1900 (Härdtle et al 2009), and heathland is now considered an EU priority habitat for conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Heathland is a traditional habitat in Western Europe (De Smidt 1979;Webb 1998) and parts of Northern America (Oberndorfer and Lundholm 2009) with very characteristic plants and animals (Delettre et al 2008;Lin et al 2007;Maes et al 2003;Telfer and Eversham 1996). In most countries, the present area covered with this vegetation type is only a fraction of the area covered around 1900 (Härdtle et al 2009), and heathland is now considered an EU priority habitat for conservation.…”
Section: Introductionmentioning
confidence: 99%
“…All lichens were sampled within 550 m of the shoreline, the same range distance to coast studied in previous research on coastal barrens in Nova Sco (Oberndorfer and Lundholm 2009), along three transects within the Chebuc Head wilderness area.…”
Section: Methodsmentioning
confidence: 99%
“…Research describing the composition of their vegetation has revealed a diverse array of vascular plants, mosses, and macrolichens in these "barren" habitats (Oberndorfer and Lundholm 2009). Lichens play an important role in coastal heathland ecosystems, often covering substantial areas (Chris tensen andJohnsen 2001, Oberndorfer andLundholm 2009). describing the gradient of lichen communit terrestrial region. However, large-scale p tion do show a maritime gradient (McCune are specific to coastal habitats (Brodo et Fletcher (1973a, b) provided an extensi pralittoral lichens in Great Britain.…”
Section: Introductionmentioning
confidence: 99%
“…They can survive and grow on the bare surface of rocks and in poor soils such as heathlands, peat lands, sand dunes, and toxic spoil heaps 10 . Selection of vegetation types appropriate for extensive green roofs often involves identifying local habitats that have characteristics in common with green roofs (shallow soil, harsh abiotic conditions) 11 ; lichens are a common component of rock barrens, dunes, and heathland habitats that can be a source of plants for green roofing projects 12, 13 .…”
Section: Introductionmentioning
confidence: 99%